2011
DOI: 10.1007/s13233-011-0101-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GMA grafted MWNTs on physical and rheological properties of PMMA-based nanocomposites by in situ polymerization

Abstract: In this study, multi-walled carbon nanotubes (MWNTs) reinforced poly(methyl methacrylate) (PMMA) nanocomposites were prepared by in situ polymerization. Glycidyl methacrylate (GMA) grafted MWNTs (GMAMWNTs) were used to improve the compatibility between the MWNTs and the PMMA matrix. The physical and rheological properties of the PMMA nanocomposites with different GMA-MWNT contents were examined. The GMA-MWNTs were embedded homogeneously into the PMMA matrix by in situ polymerization. A uniform dispersion of GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…As shown in Figure 4, the characteristic D band (1322 cm −1 ) and G band (1589 cm −1 ) in the Raman spectrum of MWCNTs gradually broaden and the G band shifts toward 1583 cm −1 as the content of EHSiPA in the hybrid increases, indicating the formation of the EHSiPA layer on the surfaces of the MWCNTs. 14 On the basis of the above analyses, it is concluded that through the sp 2 hybridization the alternating benzenoid rings and N atoms along the PA segments in EHSiPA form a conjugated structure, which tends to produce π−π interactions with the π-banded surfaces of MWCNTs, while the multi-PA chains and flexible branched chains of EHSiPA make this tendency become true. It should be noted that a very small amount of EHSiPA can be stacked firmly onto the surfaces of MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4, the characteristic D band (1322 cm −1 ) and G band (1589 cm −1 ) in the Raman spectrum of MWCNTs gradually broaden and the G band shifts toward 1583 cm −1 as the content of EHSiPA in the hybrid increases, indicating the formation of the EHSiPA layer on the surfaces of the MWCNTs. 14 On the basis of the above analyses, it is concluded that through the sp 2 hybridization the alternating benzenoid rings and N atoms along the PA segments in EHSiPA form a conjugated structure, which tends to produce π−π interactions with the π-banded surfaces of MWCNTs, while the multi-PA chains and flexible branched chains of EHSiPA make this tendency become true. It should be noted that a very small amount of EHSiPA can be stacked firmly onto the surfaces of MWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Chafidz et al [ 32 ] reported that the polypropylene-nanoclay composites prepared from masterbatch had sol-to-gel transition point, and indicated that the polymer macromolecular could not completely relax owing to the interfacial interaction between the nanoclay and polymer matrix. Besides, the value of G’ for the amino-CNT/PAN composite concentrated solutions are higher than those of PAN concentrated solutions in low frequency at the same temperature, suggesting that the network structure could be formed between the amino-CNTs and PAN macromolecular chains [ 25 , 41 , 42 ]. Moreover, it is consistent with the uniform dispersion of amino-CNTs leading to the higher storage modulus [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…After polymerization, a substantial increase of approximately 80 °C in the thermal decomposition temperature of P-GMA-NGP ( T d = 342 °C) was observed than in that of P-NGP/S synthesized by the solution-mixing method (245 °C). Compared to P-NGP/S synthesized by the solution-mixing method, a remarkable increase in the thermal stability of P-GMA-NGP composite was observed due to the strong interfacial interaction between the polymer filler through the bridging of GMA chains, which hinders the decomposition. , Moreover, a higher residue of P-GMA-NGP at 600 °C can be attributed to earlier functionalization of NGPs, which plays an important role during the degradation of nanocomposite and leads to the formation of a thermally stable product and contributes to the residue formation in the end.…”
Section: Resultsmentioning
confidence: 99%